Assessment of PM 2.5, CO₂ and NO₂ in relation with traffic density in UiTM Puncak Alam / Nursyafiqah Liyana Abdul Jabar - Abdul Jabar, Nursyafiqah Liyana (2018)
Transportation sector is one of the contributors to particulate matter 2.5 (PM 2.5), carbon dioxide (CO₂), nitrogen dioxide (NO₂) and other air pollutant emissions leading to the deterioration of air quality. Seasonal emission level between peak and non-peak periods from road traffic were studied in UiTM Cawangan Selangor, Kampus Puncak Alam and the pattern of these pollutants were measured at three bus stops within the campus by using EVM 7. Independent t-test were carried out to find the mean differences in pollutant concentrations between both periods. Concentration levels of PM 2.5 and CO₂ were significantly higher during the peak period compared to non-peak period with p-values of 0.001 and 0.001 respectively, whereas there was no significance difference in NO₂ concentration level between both period (p-value 0.425). A strong correlation between PM 2.5 (r 0.865) and CO₂ (r 0.721) with traffic density was also concluded from this study. To conclude, results from this study can provide data for evidence-based environmental policy decision making to regulate strict enforcement of environmental regulations in higher learning institutions.